Efficacy of vaptans for correction of postoperative hyponatremia: A comparison between single intravenous bolus conivaptan vs oral tolvaptan - Sunil Rajan; Pulak Tosh; Dilesh Kadapamannil; Soumya Srikumar; Jerry Paul; Lakshmi Kumar (Wolters Kluwer Medknow Publications, 2018)
Background and Aims: Hyponatremia is one of the most common electrolyte abnormality encountered in postoperative patients especially in the elderly. We aimed to assess the efficacy of single-dose intravenous conivaptan vs. oral tolvaptan therapy for correction of hyponatremia in postoperative patients. Material and Methods: This prospective randomized study was conducted on 40 patients aged 20-70 years, who had undergone major head and neck surgeries with a serum sodium level of ≤130 mEq/L and were symptomatic. Patients were randomly allocated into two equal groups. Patients belonging to group C received single intravenous bolus dose of conivaptan 20mg, whereas group T received oral tolvaptan 15mg on the first day. At 24h, if sodium correction was <4mEq/L, dose of tolvaptan was increased to 30mg in group T or an infusion of conivaptan 20mg over next 24h was started in group C. Results: Chi-square test, independent sample t-test, and paired t-test were used as applicable. Though there was no significant difference in the baseline sodium values in both groups, at 12 and 24 h group C had significantly high values. At 48h sodium values in both the groups were comparable. Intra-group analysis had shown that there was a significant increase in sodium values from the baseline at 12, 24, and 48 h in both the groups. Conclusion: Single-dose intravenous conivaptan as well as oral tolvaptan were safe and effective in correcting hyponatremia in postoperative patients. Conivaptan could be considered superior as it resulted in faster sodium correction with effective aquaresis.